Comparative evaluation of different integrated farming system models for small and marginal farmers under the Eastern Himalayas - KUMAR, RAKESH; PATRA, M K; THIRUGNANAVEL, A; DEKA, BIDYUT C; CHATTERJEE, DIBYENDU; BORAH, T R; RAJESHA, G; TALANG, H D; RAY, S K; KUMAR, MANOJ; UPADHYAY, PRAVIN KUMAR (The Indian Journal of Agricultural Sciences, 2018)
Integrated farming system (IFS) ensures efficient utilization of available farm resources, increases unit productivity and income that are pre-requisite for sustainable livelihood of small and marginal farmers. The present study was conducted to evaluate the performance of four IFS model developed in 1.0 acre area, at ICAR Research Complex for North Eastern Hill Region, Nagaland Centre, Jharnapani, Medziphema, Nagaland. The major components in IFS models were agriculture, horticulture, livestock and subsidiary components like fishery, vermicompost, mushroom and azolla. The field crops, vegetables and livestock components were included in IFS model considering topography of land, soil texture and preference for the tribal livelihood. The performance in terms of component wise productivity, profitability, employment generation and sustainability value index (SVI) were evaluated in consecutive three years (2012–2015). The combinations of subsidiary components in agriculture + horticulture + poultry + fishery in IFS model (model–4) gave the highest net returns (Rupees 32040) followed by the model with agriculture + horticulture + fishery + piggery + vermicompost (model 3) with net profits of Rupees 21230. In field crops component, cropping sequence of ricetoria- mungbean system was found to be the best in terms of productivity among the tested IFS models except in model 1. In terms of employment generation, IFS model-4 has shown maximum man-days engagement (395 days), followed by 350 days in model-3. Based on sustainability values index (SI) derived from different IFS models, maximum SVI values was recorded in model-4 (0.71) followed by model-3 (0.47). Therefore, the intensification of IFS model with crop, horticulture, fishery and livestock or poultry should be popularized among the small and marginal farmers on a larger scale, as it provide scope for higher returns, year round employment and sustainable livelihood in longer perspectives of Eastern Himalayas.